2012
DOI: 10.1152/japplphysiol.01166.2011
|View full text |Cite
|
Sign up to set email alerts
|

Titin-based stiffening of muscle fibers in Ehlers-Danlos Syndrome

Abstract: in response to the increased compliance of the extracellular matrix in muscle of TNX-deficient EDS patients, a marked intracellular stiffening occurs of the giant protein titin. The stiffening of titin partly compensates for the muscle weakness in these patients by augmenting submaximal active tension generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 41 publications
(63 reference statements)
1
26
0
4
Order By: Relevance
“…Horowits and Podolsky (1987) and Horowits and colleagues (1989) also showed that without force transmission by titin, force generation by the cross-bridges is highly inefficient because energy from crossbridge interactions is lost to thick filament displacement at the expense of longitudinal tension. Numerous other studies also show that changes in titin isoforms and consequent changes in titin-based stiffness are associated with changes in force production (Ottenheijm et al, 2012;Pulcastro et al, 2016). We suggest that the force deficit in mdm muscles is due to impaired transmission of force from the cross-bridges to the Z-lines.…”
Section: Titin Activation and The Mdm Mutationsupporting
confidence: 58%
“…Horowits and Podolsky (1987) and Horowits and colleagues (1989) also showed that without force transmission by titin, force generation by the cross-bridges is highly inefficient because energy from crossbridge interactions is lost to thick filament displacement at the expense of longitudinal tension. Numerous other studies also show that changes in titin isoforms and consequent changes in titin-based stiffness are associated with changes in force production (Ottenheijm et al, 2012;Pulcastro et al, 2016). We suggest that the force deficit in mdm muscles is due to impaired transmission of force from the cross-bridges to the Z-lines.…”
Section: Titin Activation and The Mdm Mutationsupporting
confidence: 58%
“…Single muscle fibers were isolated from the muscle biopsies and demembranated for 20 minutes in a relaxing solution containing 1% Triton X-100 at ;4°C. 4,5 Triton permeabilizes all membranous structures, allowing for activation of the sarcomere with exogenous Ca 21 and enabling study of sarcomeric function in isolation. On average, 9 fibers were prepared per biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental details have been described previously. 4,5 In brief, isolated single muscle fibers were mounted between a force transducer and a length motor. Maximum force-generating capacity was measured at a sarcomere length of 2.5 mm by activating the fibers in a saturating [Ca 21 ] solution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations